Prevalence, bacterial load, and genomic characterization of Vibrio parahaemolyticus in freshwater-farmed Litopenaeus vannamei from China - Shan, Feifei; Li, Weiwei; Chu, Zunhua; Hou, Peibin; Sun, Na; Li, Ronghua; Liu, Xuejie; Chen, Weiwei; Zhong, Ling; Yan, Shaofei; Cui, Shenghui; Guo, Yunchang (Frontiers in Microbiology, 2025)
Shrimp was the leading food vehicle for Vibrio parahaemolyticus outbreaks in China, yet studies on V. parahaemolyticus in globally predominant farmed shrimp (Litopenaeus vannamei) - particularly in freshwater culture remain limited. This study aimed to investigate and evaluate the contamination of V. parahaemolyticus in freshwater-farmed marine shrimp (L. vannamei) in China. The prevalence and bacterial load of V. parahaemolyticus in shrimps were assessed by China China National Standard GB 4789.7-2013 and isolates were obtained for genomic analysis. The prevalence of V. parahaemolyticus in shrimp samples was 39.1% and the bacteria load ranged from 3.6 MPN/g to 24,000 MPN/g. Analysis on isolates demonstrated that 75.8% (94/124) were assigned to 28 sequence types (STs), whereas 24.2% STs were unknown. All isolates harbored 24 antibiotic resistance genes (ARGs), of which tet(34), tet(35), and blaCARB were harbored in all isolates. There was a significant correlation between blaCARB types and STs, with isolates sharing identical STs carried the same blaCARB variant. The trh+ isolates (9.7%, 12/124) was simultaneously coexisted with hlyB and hlyC. All four ST79 strains harbored trh/hlyB/hlyC and blaCARB_46. Our findings elucidated the contamination of V. parahaemolyticus in freshwater-farmed L. vannamei, with heavy bacteria load in Fujian province. The emergence of specific ST co-harboring critical virulence genes and ARGs indicating the necessity for targeted surveillance and specified control in aquaculture systems.